A systematic literature review of consuming-stage interventions in addressing food waste reduction in lower- and upper-middle-income countries - Rusyda, Akifa Laila (Journal of Community Empowerment for Health, 2024)
Introduction: Over a billion tons of food are wasted annually. There was much evidence in higher-income countries towards food waste reduction in consumption level. Conversely, some food waste volume is rising worldwide, particularly in lower- and middle-income countries. In order to improve understanding of how to minimize food waste during the consumption stage, the present literature review aimed to synthesize food-waste reduction interventions at the consumption level in lower- to upper-middle-income countries. Methods: The study used the Google Scholar database and followed PRISMA guidelines. Results: Three hundred sixty-five articles were retrieved from the database searched. The final round summarized 13 implemented food waste reduction interventions at the consumer stage. The finding shows also there were several main intervention types applied, including campaign (n=6), technology (n=4), policy (n=2), and others conducted in households (n= 9; 70 percent), restaurants (n= 2; 15 percent), and university/ college (n= 2; 15 percent). Conclusion: Policy is still a fundamental determining intervention of the effectiveness of food waste reduction at the consumption level. Furthermore, a framework suggests that community-based education may be applied as a consumption-level intervention to minimize food waste, which is appropriate for the community empowerment approach in lower- and upper-middle-income countries. Furthermore, intervention using composting eco-friendly technology also required innovation and community support.